High compression strength single network hydrogels with pillar[5]arene junction points. Issue 2 (31st October 2019) - Xu, Xiaowen; Jerca, Florica Adriana; Van Hecke, Kristof; Jerca, Valentin Victor; Hoogenboom, Richard
Abstract : This study describes a straightforward and versatile approach for synthesizing poly(2-isopropenyl-2-oxazoline) hydrogels with tunable properties by using a bifunctional macrocyclic pillar[5]arene host having two carboxylic acid groups as crosslinker. Abstract : The present study highlights a straightforward and versatile strategy for the synthesis of strong poly(2-isopropenyl-2-oxazoline) hydrogels with tunable properties by using a bifunctional macrocyclic pillar[5]arene host having two carboxylic acid groups as cross-linker. This new strategy provides access to materials with tailored properties from soft and flexible to rigid and strong. The mechanical properties and water uptake of the hydrogels could be effortlessly controlled during the synthesis step through variation of the cross-linker content and after cross-linking by guest–host interactions. The hydrogels displayed strongly enhanced mechanical properties ( i.e., compression and tensile modulus, energy dissipation, stress at break and storage modulus) compared to their counterparts cross-linked with linear dicarboxylic acids. The remarkable properties of the pillar[5]arene cross-linked hydrogels were assigned to the transfer of the external stress to the rigid and bulky pillar[5]arene residues that contribute to the overall dimensional stability of the hydrogels and allow energy dissipation. Moreover, we demonstrate the applicability of these materials for water purification. The hydrogels showed high adsorption performance for phenols and dyes such as methylene blue and methyl red and they could be easily regenerated, by washing with an organic solvent for reuse.